Greenwashing as a Crime and the Urgency of Redesigning the Environmental Criminal Law Paradigm - Zico Junius Fernando; Wevy Efticha Sary; Ahmad Wali; Ariesta Wibisono Anditya (University of Jember, Indonesia, 2025)
Greenwashing, a deceptive practice wherein corporations falsely present their products, services, or policies as environmentally friendly, has emerged as a serious threat to environmental protection and consumer trust in the era of sustainable development. This paper argues that greenwashing should be recognised not merely as an ethical or regulatory violation but as a criminal offence within the framework of environmental criminal law. Through a normative-juridical approach combined with a comparative analysis of legal frameworks in various jurisdictions, this study explores the limitations of current civil and administrative sanctions in deterring greenwashing practices. The analysis reveals that the absence of criminal liability has allowed corporations to manipulate sustainability narratives without facing substantial legal consequences. By examining the socio-legal harms of greenwashing, including environmental degradation, market distortion, and erosion of public confidence, this paper advocates for a paradigm shift in environmental law enforcement. It proposes the integration of greenwashing as a distinct criminal act under environmental law, emphasising principles such as strict liability, corporate criminal responsibility, and the need for restorative justice mechanisms. The study concludes with policy recommendations for legal reform that align with the principles of ecological justice and sustainable governance, reinforcing the urgency to criminalise greenwashing as part of a broader effort to protect both the environment and the rights of consumers.